THE EFFECT OF STORE ATMOSPHERE, FASHION INVOLVEMENT, AND SHOPPING ENJOYMENT ON IMPULSIVE BUYING FOR FEMALE IN MANADO CITY (CASE AT STROBERI) - Kaseger, Angeli; Massie, James D.D.; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2020)
Abstract: Impulsive buying is the tendency of a customer to buy goods and services without planning in advance, it is usually triggered by emotions and feelings. There are some factors that affected customers to buy something impulsively such as Store Atmosphere, tangible part of store includes theme colors, store layout, and eye-catching decoration. Fashion Involvement also has good impact to make customers buy goods by following the trends. In the other hand, customers are usually buy things impulsively with their feelings, and emotion of joy which called Shopping Enjoyment. The aim of this research is to find out the effect of Store Atmosphere, Fashion Involvement, and Shopping Enjoyment on Impulsive Buying for female in Manado city.Â This is a quantitative research and using Multiple Linear Regression as method to analyze the data. The population of this research is female customers of Stroberi. This research use questionnaire as an instrument to get the data, with the sample size is 100 respondents. This research showed that Store Atmosphere, Fashion Involvement, and Shopping Enjoyment simultaneously influence to impulsive buying while partially, fashion Involvement have significant influence to impulsive buying and Store Atmosphere and Shopping Enjoyment do not have a significant influence to Impulsive Buying. This study suggest that the manager of Stoberi to improve their Store Environment and services to make customers make unplanned purchases.Â Keywords: Impulsive buying, store atmosphere, fashion involvement, shopping enjoyment